Analisis Sistem Pengendalian Internal dalam Mewujudkan Transparansi dan Akuntabilitas pada Badan Kepegawaian Daerah - Setya Arumitha, Farida; Isharijadi, Isharijadi; Styaningrum, Farida (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p07, 2020)
This study aims to analyze and describe how the internal control system creates transparency and accountability. The study was conducted using qualitative descriptive methods. The data used in this study include primary data and secondary data obtained from interviews and documentation. The results showed that the internal control system carried out in BKD was already good and could realize transparency and accountability but for the elements in the internal control system that is risk assessment still needed to be carried out more optimally because it could not yet realize good program accountability, which can be seen from finding that the program has been determined despite achieving performance achievements of 90% - 100% with a very good predicate, but there are still a number of programs that have not met the target due to external factors. Keywords: Internal Control System; Transparency; Accountability.